The Relationship Between Training Concentration With the Accuracy of Passing Futsal Club Bomber (FA) Jakarta - Syamsulrizal, Syamsulrizal; Iqbal, Muhammad (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2022)
The purpose of the study. aiming to find out whether there is a relationship between the level of training concentration and the provision of futsal passing at the BOMBER FA club, Sawangan. Materials and methods. The method used in this study is the correlation method. The population in this study were the participants of the BOMBER FA futsal club, which amounted to 20 people. The sample is part or representative of the population under study. 3The sample in this study were participants of the BOMBER FA club, which amounted to 20 people. Results. According to the Product Moment correlation analysis, the value of rcount is 0.675 > rtable 0.532 and a significance value of 0.008 <0.05, which means